2020
DOI: 10.1186/s13071-020-04477-5
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular bacterium Rickettsia rickettsii exerts an inhibitory effect on the apoptosis of tick cells

Abstract: Background Rickettsia rickettsii is a tick-borne obligate intracellular bacterium that causes Rocky Mountain spotted fever, a life-threatening illness. To obtain an insight into the vector–pathogen interactions, we assessed the effects of infection with R. rickettsii on the proteome cells of the tick embryonic cell line BME26. Methods The proteome of BME26 cells was determined by label-free high-performance liquid chromatography coupled with tandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Martins and colleagues demonstrated that Rickettsia rickettsii inhibited apoptosis in tick cells ( 41 ). In contrast, our previous study showed that the cleavage of caspase-3 promoted DNA fragmentation and led to apoptosis in Rickettsia parkeri -infected tick cells, suggesting species-specific interactions of rickettsiae with tick cells.…”
Section: Resultsmentioning
confidence: 99%
“…Martins and colleagues demonstrated that Rickettsia rickettsii inhibited apoptosis in tick cells ( 41 ). In contrast, our previous study showed that the cleavage of caspase-3 promoted DNA fragmentation and led to apoptosis in Rickettsia parkeri -infected tick cells, suggesting species-specific interactions of rickettsiae with tick cells.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstrated effects on the mouse neuron of a R. helvetica infection, differ to some extent from previously reported findings in infection of human monocytes with R. helvetica, where TNFα production was induced and the rickettsia bacteria both replicated and survived in the monocyte's cell plasma without causing apoptosis of the host cell, which instead theoretically enables the infection to also spread to the CNS by crossing the blood-brain barrier [6,14]. In the case of R. rickettsii, it has also been shown that the bacterium can modulate the proteome in its host cell, tick embryonic cells (BME26), including proteins inscribed with apoptosis, and exert an inhibitory effect on the apoptosis, which helps ensure its proliferation in that cell [37]. The spotted fever group of rickettsiae, in contrast to most of the typhus group, have the capacity to move in an intra-and intercellular fashion that involves protrusion formation, engulfment and vacuolar escape [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of caspase-3 exerted a detrimental effect on rickettsial proliferation and its inhibition increased bacterial growth. Also, the expression of other negative regulators of apoptosis changed during the course of infection (Martins et al 2020 ). In the case of H .…”
Section: Modulation Through the Interference With Caspasesmentioning
confidence: 99%